Diagnosis of spontaneous hyperadrenocorticism in dogs. Part 1: Pathophysiology, aetiology, clinical and clinicopathological features. (October 2019) - Bennaim, Michael; Shiel, Robert E.; Mooney, Carmel T.
Highlights: The diagnosis of canine hyperadrenocorticism (HAC) is based on multiple diagnostic modalities rather than a single test. Decisions to test adrenal function for HAC should not be solely based on presence or absence of clinicopathological change. The prevalence of clinical and clinicopathological findings in HAC does not appear to have changed over the last 40 years. Some signalment, clinical and clinicopathological features indicate substantially increased or decreased likelihood of HAC. Abstract: Hyperadrenocorticism is a relatively common endocrine disorder in dogs. It occurs as a result of a functional pituitary or adrenal tumour, although other causes have been rarely reported. Canine hyperadrenocorticism has been extensively described but diagnosing this disease remains challenging. Few studies have investigated the clinical and clinicopathological features helpful in differentiating dogs with hyperadrenocorticism from dogs in which the disease is suspected but eventually excluded. Ultimately the diagnosis is based on a combination of multiple pieces of information emanating from the signalment, history, clinical findings, and a variety of diagnostic tests. The first part of this review aims to critically appraise the available data on epidemiology, clinical and laboratory features of naturally occurring canine hyperadrenocorticism.